A Humanoid Robot on the Basis of Modules Controlled Through a Serial Half-duplex UART Bus - Matoušek, Sebastian; Maršálek, Roman (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
Just a few decades ago the concept of humanoid robots assisting us at work would be something better suited for a movie plot than as a business plan. However, nowadays tests of such robots are already being performed, with big companies exploring the possibilities of such robots assisting in warehouses, robotic assistants roaming around airports directing lost passengers and more. In the future, such robots could very well be employed in many more areas of work – thanks to their construction being similar to humans, they integrate well into our everyday environment and make cooperation more intuitive. This thesis is the result of an attempt at building a small-scale humanoid robot. It expands upon the thesis ”Bipedal Walking Robot” [1] from last year, which described the process of building a two-legged robot capable of walking, at that time still lacking arms and a head, however. This thesis focuses on the expansion of the robot, mainly the addition of the upper limbs and a head missing in the previous project, thus finally creating a humanoid robot. Furthermore, a custom ecosystem of modules on the basis of the ESP32-C3FH4 microcontroller is discussed; communicating through a serial half-duplex UART bus, these modules were used to construct the upper body, smoothen the movement of the robot, and collect additional data about the robots movement. Such modules can be further used in other projects requiring the usage of numerous interconnected, yet independent, electronics parts.
Keywords: Arnold Biped Robot; humanoid robot; bipedal walking robot; intelligent servomotor; ESP32; ecosystem of modules